Archiving Indigenous technical knowledge (ITK) based ethnomedicinal practices among tribal communities in the Nilgiris: A perception analysis - Pooja, B M; Anandaraja, N; Fernandaz , C C; Balasubramaniam , P; Selvi, R G (Plant Science Today, 2025)
Ethnomedical practices of the tribal community in the Nilgiris district were documented and analyzed to assess their knowledge and perception of Indigenous Technical Knowledge (ITK) and to understand the constraints faced in utilizing the same. This study, in doing so, presents a discussion of the interface of socioeconomic variables with indigenous traditional knowledge to highlight the determinants that facilitate the retention and transmission of traditional medicine knowledge in these communities. The present study adopted an exploratory research design. Data were collected from six tribal communities through snowball sampling, with a total of 120 respondents in two blocks of the Nilgiris district. While analyzing the relationships, the socio-economic characteristics were correlated with the knowledge levels and constraints on traditional medicinal practices. Some of the other tools that were applied to these studies included rank-based quotients and multiple regression analysis. Findings indicate that a major section of the tribal population has a medium to low level of knowledge of ITK, with perception varying due to age, income, and information availability. Superstitions, extraction of scientific principles involved in allopathic science, and most of all, lack of interest shown by the younger generation are major factors inhibiting the spread of the practices. Diagnosing these challenges with specified community engagement strategies, education, and access to traditional medicine is thus the highway to sustaining this invaluable cultural heritage. The research suggests a holistic approach to conserve ITK and traditional medicine by marrying modern healthcare with traditional practices to maintain their relevance for posterity.